Personality Development of Miles In John Green’s Looking For Alaska - Mawaddah, Fitrotul (English Literature Study Program, 2024)
This research aims to analyze the personality development of the main character in the novel Looking For Alaska by John Green. Looking For Alaska by John Green was published by The United States of America in 2005. The novel is the main object of this research. This thesis was carried out to analyze personality development and the factors causing the personality development of the main character. This research aims to find out how Miles is described in the novel and his personality development as well as the factors that influence Miles' personality development. The problem formulation in this research is: What is Miles' personality described in Looking For Alaska? How is Miles' personality development described in Looking For Alaska? What are the causes of Miles' personality development described in Looking For Alaska? This research data was obtained from the novel Looking For Alaska written by John Green using reading and note-taking techniques. To achieve the research objectives, the author uses literary criticism in analyzing the novel. Then, the author uses a psychological approach and personality development theory by Elizabeth Hurlock. The results of this research show three findings in response to the problem statement. The first is Miles' personality. Researcher found four personalities in Miles, namely submissive, stolid, unsocial, and disciplined. The second is some of the personality developments that Miles experiences in the novel and the third is the factors that cause Miles' personality development. Researcher found that Miles is lying, irritable, social, and naughty. Miles' personality development was caused by an important person, namely Colonel and Alaska.